Gender Transition Treatment in Adolescents: A Literature Review of the Effectiveness and Risks of Medical Interventions - Lestari, Mugi; Saefullah, Rifki (International Journal of Health, Medicine, and Sports, 2025)
Transgender and gender non-binary (TGD) youth face complex psychosocial challenges, including increased risk of mental health disorders due to gender identity incongruence with biological characteristics. One approach used to support the gender affirmation process is through medical interventions in the form of hormone therapy and other medical procedures. This article aims to review the scientific evidence related to the benefits and risks of medical interventions in TGD youth, with a focus on short-term and long-term impacts on mental health, physical health, and quality of life. The method used is a systematic literature review with a critical analysis of various scientific publications from international journals indexed by Scopus and PubMed over the past ten years. The results of the review indicate that medical interventions, such as puberty blockers and hormone therapy, have the potential to provide significant benefits in reducing gender dysphoria and improving mental health in the short term. However, there is limited evidence regarding safety and long-term effects, including risks to bone mineral density, cognitive function, and potential fertility disorders. In addition, there is variation in policies between countries in implementing these medical interventions, reflecting differences in ethical, legal, and cultural perspectives. The conclusion of this article emphasizes the need for a holistic, evidence-based approach that takes into account psychosocial aspects and individual human rights in providing health services to TGD adolescents. Longitudinal studies with stronger designs are urgently needed to understand the long-term impact of medical interventions and support appropriate clinical decision-making. These findings are expected to be a reference for health practitioners, policy makers, and the community in understanding health care issues for transgender and gender non-binary adolescents.